Fixed Points of Monotone Total Asymptotically Nonexpansive Mapping in Hyperbolic Space via New Algorithm - Kalsoom, Amna; Rashid, Maliha; Sun, Tian-Chuan; Bibi, Amna; Ghaffar, Abdul; İnç, Mustafa; Aly, Ayman A. (Wiley, 2021)
In this article, we consider an extensive class of monotone nonexpansive mappings and introduce a new iteration algorithm to approximate the fixed point for monotone total asymptotically nonexpansive mappings in the framework of hyperbolic space. Faster convergence and stability results are proved for that iteration; also, fixed point is approximated numerically in a nontrivial example by using MATLAB.
Keywords: Iteration; Approximation